Integrated multi-omics analysis reveals the positive leverage of citrus flavonoids on hindgut microbiota and host homeostasis by modulating sphingolipid metabolism in mid-lactation dairy cows consuming a high-starch diet - Yuchao Zhao; Shiqiang Yu; Huiying Zhao; Liuxue Li; Yuqin Li; Ming Liu; Linshu Jiang (Microbiome, 2023)
Abstract Background Modern dairy diets have shifted from being forage-based to grain and energy dense. However, feeding high-starch diets can lead to a metabolic disturbance that is linked to dysregulation of the gastrointestinal microbiome and systemic inflammatory response. Plant flavonoids have recently attracted extensive interest due to their anti-inflammatory effects in humans and ruminants. Here, multi-omics analysis was conducted to characterize the biological function and mechanisms of citrus flavonoids in modulating the hindgut microbiome of dairy cows fed a high-starch diet. Results Citrus flavonoid extract (CFE) significantly lowered serum concentrations of lipopolysaccharide (LPS) proinflammatory cytokines (TNF-α and IL-6), acute phase proteins (LPS-binding protein and haptoglobin) in dairy cows fed a high-starch diet. Dietary CFE supplementation increased fecal butyrate production and decreased fecal LPS. In addition, dietary CFE influenced the overall hindgut microbiota’s structure and composition. Notably, potentially beneficial bacteria, including Bacteroides, Bifidobacterium, Alistipes, and Akkermansia, were enriched in CFE and were found to be positively correlated with fecal metabolites and host metabolites. Fecal and serum untargeted metabolomics indicated that CFE supplementation mainly emphasized the metabolic feature “sphingolipid metabolism.” Metabolites associated with the sphingolipid metabolism pathway were positively associated with increased microorganisms in dairy cows fed CFE, particularly Bacteroides. Serum lipidomics analysis showed that the total contents of ceramide and sphingomyelin were decreased by CFE addition. Some differentially abundant sphingolipid species were markedly associated with serum IL-6, TNF-α, LPS, and fecal Bacteroides. Metaproteomics revealed that dietary supplementation with CFE strongly impacted the overall fecal bacterial protein profile and function. In CFE cows, enzymes involved in carbon metabolism, sphingolipid metabolism, and valine, leucine, and isoleucine biosynthesis were upregulated. Conclusions Our research indicates the importance of bacterial sphingolipids in maintaining hindgut symbiosis and homeostasis. Dietary supplementation with CFE can decrease systemic inflammation by maintaining hindgut microbiota homeostasis and regulating sphingolipid metabolism in dairy cows fed a high-starch diet. Video Abstract